2017
DOI: 10.17305/bjbms.2017.2259
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status, serum lipid concentrations, and vitamin D receptor (VDR) gene polymorphisms in Familial Mediterranean fever

Abstract: Vitamin D (VitD) is critical for the regulation of inflammatory processes, and VitD deficiency has been linked to several chronic inflammatory disorders. We aimed to investigate the concentrations of serum 25(OH)D3, lipid parameters, and three known VDR polymorphisms (BsmI, FokI, and TaqI) in patients with Familial Mediterranean fever (FMF), an autosomal recessive autoinflammatory disease. The study included 123 FMF patients and 105 controls. Seventy patients had no attack (group 1), 30 had 1-2 attacks (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Moreover, the FokI SNP GG genotype-FF variant has been associated with cardiovascular disease in adult population (32). By contrast, other studies found no relationship between FokI SNPs and serum lipid levels (33,34). Taken together, our results suggest that the functional effects of FokI SNP might be gene and/or cell type-specific and may also be age-and gender-dependent.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, the FokI SNP GG genotype-FF variant has been associated with cardiovascular disease in adult population (32). By contrast, other studies found no relationship between FokI SNPs and serum lipid levels (33,34). Taken together, our results suggest that the functional effects of FokI SNP might be gene and/or cell type-specific and may also be age-and gender-dependent.…”
Section: Discussioncontrasting
confidence: 84%
“…Among significant aspects influencing the status of vitamin D in the body, we should also mention obesity, low levels of physical activity (30)(31)(32) and smoking cigarettes (33) . For example, it was shown that obese men have a higher vitamin D deficiency index than men with normal body weight (27) .…”
Section: Sources Of Vitamin D and Factors Affecting Its Synthesismentioning
confidence: 99%
“…[15] In FMF patients, it was reported that vitamin D levels were lower compared to controls and low vitamin D levels could also trigger the FMF attacks. [39–41] Although we found that vitamin D levels were low in FMF patients and healthy subjects, there was no significant difference in vitamin D levels between groups. Furthermore, there was also no correlation between vitamin D levels and osteopontin, CIMT and any atherosclerotic indices.…”
Section: Discussionmentioning
confidence: 66%